2014
DOI: 10.1002/wsbm.1268
|View full text |Cite|
|
Sign up to set email alerts
|

Integrating omics into the cardiac differentiation of human pluripotent stem cells

Abstract: Time-dependent extracellular manipulations of human pluripotent stem cells can yield as much as 90% pure populations of cardiomyocytes. While the extracellular control of differentiation generally entails dynamic regulation of well-known pathways such as Wnt, BMP, and Nodal signaling, the underlying genetic networks are far more complex and are poorly understood. Notably, the identification of these networks holds promise for understanding heart disease and regeneration. The availability of genome-wide experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…The cardiomyogenic differentiation efficiency was also confirmed by comparative proteomic data (Table S1, Supporting Information). Protein ratios of two markers were monitored, OCT4 for hiPSCs and MYL7 for CMs . OCT4 levels decreased by 0.33 and 0.14‐fold in CPCs and CMs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiomyogenic differentiation efficiency was also confirmed by comparative proteomic data (Table S1, Supporting Information). Protein ratios of two markers were monitored, OCT4 for hiPSCs and MYL7 for CMs . OCT4 levels decreased by 0.33 and 0.14‐fold in CPCs and CMs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Like their mRNA expression pattern, the differentiation markers OCT4 and MYL7 were altered in CMs as determined by quantitative proteomic analysis. Furthermore, we detected several differentiation indicators known as cardiomyocyte‐specific markers from the volcano plot analysis, including stage‐specific molecules, which can be used to distinguish the differentiation stages, such as MYH6, MYH7, HTNT1, GATA4, and DES for CMs and OCT4 for hiPSCs …”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that microRNAs (miRs) and cardiac transcription factors (TFs), such as miR-200c, and a set of GATA4/6, NKX2-5, TBX5, HEY2, and HAND1/2 can cooperatively regulate the expression of genes critical for cardiac development and function ( Poon et al, 2011 ; Poon et al, 2013 ; Cerutti et al, 2014 ; Rojas-Munoz et al, 2014 ; Kathiriya et al, 2015 ; Poon et al, 2018 ). To investigate if these regulatory factors could contribute to the differential expression of genes involved in maturation between “1 + 2 + 2” and “2 + 2” cultures ( Figure 3 ), we identified binding sites of the cardiac TFs on the promoters of these ‘maturation genes’.…”
Section: Resultsmentioning
confidence: 99%
“…Among these are MESP1, which acts as a master regulator of cardiac lineage commitment [ 3 , 4 ]. The cardiac TFs GATA4, GATA6, NKX2-5, MEF2A/C, SRF, ISL1, TBX5, HAND1 and HAND2 subsequently play critical roles in regulation of early embryonic cardiogenesis [ 5 , 6 ]. The TFs HEY2 or NR2F2 and TBX5 direct ventricular or atrial identity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%